Empowering technologies?: introducing participatory geographic information and multimedia systems in two Indonesian communities - Corbett, J. (University of Victoria, 2003)
Inclusion of local knowledge in decision-making is recognized as important for land use planning. However, this is prevented by communication constraints. Increasingly local communities throughout the world are using community mapping and simple Geographic Information Technologies (GIT) to communicate information about traditional lands to decision-makers. This corresponds to the trend, primarily in North America, for practitioners to apply Geographic Information Systems (GIS) technologies in public participation settings. Claims have been made that use of Public Participation Geographic Information Systems (PPGIS) by disadvantaged groups can be empowering. However, others claim that PPGIS is disempowering due to the cost and complexity of the technologies, inaccessibility of data, restrictive representation of local geographic information, and the low level of community participation. The research described in this thesis sets out to contribute to the debate regarding PPGIS and empowerment. Participatory Geographic Information and Multimedia Systems (PGIMS) technologies were developed for this project in an attempt to overcome the weaknesses of PPGIS described above. A PGIMS project was introduced into two communities in West Kutai, Indonesia. The PGIMS technologies enabled local communities to gather information using a digital camera and video camera, and store, manage and access it. A participatory process ensured that communities made all decisions related to the project and were trained in the necessary technical skills. Functional PGIMS were created in both participating villages. These PGIMS were relevant to the communities’ needs to record information for future generations and communicate information about boundaries and land use to outsiders. The research question addressed in this thesis was: How does the PGIMS project empower or disempower local communities? The author developed a working definition of empowerment to enable evaluation: empowerment is an increase in social influence or political power. Furthermore the author determined that empowerment is achieved through a combination of internal changes in an individual or community as well as external factors. These are defined as changes in ‘empowerment capacity’. This thesis presents a framework to structure an analysis of empowerment. It enabled the author to examine how four catalysts related to the PGIMS project empowered and disempowered, as well as increased and decreased empowerment capacity of the individual and community. Catalysts included the information contained within the PGIMS, the participatory process used, the technological skills acquired and the tools applied to develop the PGIMS. Qualitative data were gathered in the field using participant observation, semi-structured interviews and questionnaires. Data were categorised into indicators of increased or decreased empowerment and empowerment capacity. These indicators were sorted into the relevant cells of the framework. The empowerment framework offered a logical structure to categorize the data and enable an analysis of how different components of the PGIMS project impacted individuals and communities. It was also useful for differentiating between empowerment and empowerment capacity impacts. There were weaknesses with the methods and framework. These included the inability to determine the extent to which the PGIMS project contributed to the observed indicators relative to other influences; the difficulty of interpreting the data to create indicators, and the difficulty of measuring some indicators or defining their relative importance in the framework. This research concluded that the PGIMS project empowered participating individuals and communities, and also increased their empowerment capacity, but it is difficult to determine how lasting or significant this is. It also disempowered individuals and communities. Individuals were more empowered by skills and processes, while communities more empowered by information and tools. The benefits of individual empowerment can conflict with community empowerment. Empowerment in the PGIMS project was highly influenced by pre-existing conditions in individuals and communities.